Pediatric Ventricular Assist Device Support in the Netherlands. Issue 3 (May 2020) - Rohde, Sofie; Antonides, Christiaan F. J.; Muslem, Rahatullah; de Woestijne, Pieter C. van; der Meulen, Marijke H. van; Kraemer, Ulrike S.; Dalinghaus, Michiel; Bogers, Ad J. J. C.
Background: This study aimed to evaluate the changes in heart transplantation (HTx) waiting list mortality following the introduction of the Berlin Heart EXCOR (BH EXCOR) in the Netherlands, as well as the occurrence of adverse events in these children. Methods: A retrospective, single-center study was conducted including all pediatric patients (≤18 years) awaiting HTx. Patients were grouped in two eras based on availability of the BH EXCOR in our center, era I (1998-2006; not available) and era II (2007 to July 31, 2018; available). Results: In total, 87 patients were included, 15 in era I and 72 in era II. Extracorporeal membrane oxygenator support was required in 1 (7%) patient in era I and in 13 (18%) patients in era II. Overall mortality (7/15 in era I vs 16/72 in era II; 47% vs 22%, P = .06) and transplantation rates (8/15 in era I vs 47/72 in era II; 53% vs 65%, P = .39) did not differ significantly. Eleven (39%) patients of the pediatric ventricular assist device (VAD) population died, with the predominant cause being cerebrovascular accidents (CVAs) in eight (29%) patients. Furthermore, 14 (50%) of the pediatric VAD patients survived to transplantation. Adverse events most frequently occurring in VAD patients included CVA in 14 (50%), mostly (68%) within 30 days after VAD implantation, and bleeding requiring rethoracotomy in 14 (50%), all within 30 days after VAD implantation. Conclusions: The introduction of the BH EXCOR has positively impacted the survival of pediatric patients with end-stage heart failure in our center. The predominant cause of death changed from end-stage heart failure in era I to CVA in era II. We emphasize the need for large prospective registry–based studies.